A SYSTEMATIC MAPPING STUDY OF CYBERSECURITY VULNERABILITIES, ATTACKS, AND MITIGATION STRATEGIES - Khanna, Kanika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
For the intention of fortifying cyber applications and fending off significant security hazards, cybersecurity exploration has witnessed a remarkable upsurge in recent years. Identifying and examining prevalent cybersecurity vulnerabilities is the main aim of this investigation. To reach that destination, scientists embarked on a comprehensive cartography inquiry, which led to the recognition and assessment of 69 primary investigations. We discovered the most widespread security vulnerabilities after performing an extensive examination of the selected investigation. The location of publishing, country of publication, significant targeted infrastructure, applications, etc. have all been examined and showcased through data amalgamation. The results illustrate that the previously mentioned security methods simply strive to enhance security in overall, and that additional investigation is necessary to empirically confirm and practically implement the suggested resolutions. Moreover, we discovered that the majority of the investigation we incorporated in our examination concentrated on just a handful of the most common security vulnerabilities, such as social engineering, denial-of-service assaults, and malicious software. Nevertheless, additional effort must be exerted in this domain to ensure scholars and professionals acquire an enhanced comprehension of the utmost urgent cybersecurity weaknesses, targeted/exploited applications, alleviation methods, and frameworks.